The Impact Of Indonesia-Malaysia Bilateral Cooperation On The West Kalimantan Border In The Education Field - Bahterayudha, Bahterayudha; Sari, Suwarti; Nurdin, Iing (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to analyze the impact of Indonesia-Malaysia bilateral cooperation on the border of West Kalimantan in the field of education. This study uses qualitative methods with data collection techniques through interviews, observation, and documentation studies. Research respondents consisted of government officials, educators, and students who were involved in bilateral cooperation in the field of education. The results of the study show that bilateral cooperation between Indonesia and Malaysia in the field of education at the border of West Kalimantan has had both positive and negative impacts. Positive impacts include improving the quality of education, increasing educational accessibility, and increasing bilateral relations between the two countries. While the negative impacts include the gap between students who benefit and those who do not benefit, imbalances in program planning and management, as well as challenges in the implementation of bilateral cooperation. Therefore, efforts are needed to improve program management and the implementation of bilateral cooperation in the education sector so that it can have a greater positive impact on both countries and the people on the border of West Kalimantan.